ANALYSING THE EFFECT OF TEACHING ISLAMIC STUDIES IN PUBLIC PRIMARY SCHOOLS IN ADAMAWA STATE - Yakubu, Aminu; Barkindo, Muhammad Adamu; Aliyu, Yunusa; Hayatu, Chubado (IJRDO - Journal of Social Science and Humanities Research, 2022)
Islamic studies is one of the subject taught in Nigerian primary schools. It has been observed that there are many problems associated with the teaching of the subject in public primary schools. This research intends to explore the problems and suggest some possible solutions. The focus is mainly on some selected primary schools in Adamawa State. Structional Questionnaire and interviews were used to collect data for the study. Data was analysed by using simple percentages. The study revealed that there are various factors that affect the effective teaching of Islamic studies in public primary schools. These include among others inadequacy of qualified and trained teachers, absence of refresher course, lack of adequate teaching aids and textbooks. The study suggest that teachers of Islamic studies to be involved in the planning and review of the curriculum and government should be organizing refresher courses and workshops for Islamic studies teachers.